PREDICTION OF THE VAPOR-LIQUID DISTRIBUTION CONSTANTS FOR VOLATILE NONELECTROLYTES IN WATER UP TO ITS CRITICAL TEMPERATURE - Plyasunov A.V.; Shock E.L. (My University, 2003)
The distribution of solutes between coexisting liquid and vapor phases of water can be expressed by the distribution constant, KD, defined as where y and x stand for the mole fraction concentrations of a solute in vapor and liquid phases, respectively. Research reported here is concerned with the prediction of this property, KD, for volatile nonelectrolytes, over the whole temperature range of existence of the vapor–liquid equilibrium for water, i.e. from 273 K to the critical temperature at 647.1 K. A simple empirical method is proposed to extrapolate the values of KD from 298 K to 500–550 K. Calculations at higher temperatures are based on the theoretical relation that establishes the proportionality between RTlnKD and the Krichevskii parameter, AKr, which is the single most important property of a solute at near-critical conditions, and can be evaluated using the method proposed here. The comparison of predicted and experimental values of KD and AKr for a few well-studied solutes reveals the satisfactory performance of the proposed method. It appears that the accuracy of predictions in the framework of this method is limited mainly by the accuracy of the values of the thermodynamic functions of hydration of solutes at 298 K, and that the best way to improve the quality of predictions of KD and AKr is to increase the inventory of accurate calorimetric enthalpy and heat capacity data for aqueous solutes at 298 K. We stress that the values of the Krichevskii parameter, such as those generated in this study, are of crucial importance for reliable predictions of the chemical potential and its derivatives (V2o, Cp2o) for aqueous solutes at near-critical and supercritical conditions. Values of KD and AKr are predicted for many inorganic volatile nonelectrolytes and some halogenated derivatives of methane and ethene. We show that both ln KD and AKr for aqueous organic solutes follow group additivity systematics, and we derive a set of corresponding group contribution values for several functional groups (material point, CH3, CH2, CH, C, C = C, HC = CH, C≡C, HCar, Car, Cfus, OH, O, S, SH, CO, COO, COH, COOH, CN, F, Cl, Br, NH2, NH, N, etc.).